2013
DOI: 10.9738/intsurg-d-13-00019.1
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Schwannomas: Case Report With Literature Review

Abstract: Schwannomas are rare tumors that arise from Schwann cells in neural sheaths. They are commonly found in the central nervous system, spinal cord, or peripheral nerves of the body. Occasionally, they occur in the gastrointestinal tract, with the stomach being the most common site. However, colorectal and retroperitoneal schwannomas are very rare. Preoperative diagnosis is often difficult and definitive treatment entails surgical excision. We herein present 3 cases of intraabdominal schwannomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
16
0
3
Order By: Relevance
“…Despite the existence of advanced imaging modalities, such as ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI), only a few cases of RSs are diagnosed prior to resection ( 9 ). Diagnosis is usually made following excision and histological examination ( 10 ). Surgery is the primary treatment choice for RS; however, in malignant RS, a poor prognosis, such as neurofibromatosis type 1 (von Recklinghausen's disease), which is characterized by the occurrence of visceral neoplasms along with abnormal and numerous skin diseases ( 11 , 12 ), may occur ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of advanced imaging modalities, such as ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI), only a few cases of RSs are diagnosed prior to resection ( 9 ). Diagnosis is usually made following excision and histological examination ( 10 ). Surgery is the primary treatment choice for RS; however, in malignant RS, a poor prognosis, such as neurofibromatosis type 1 (von Recklinghausen's disease), which is characterized by the occurrence of visceral neoplasms along with abnormal and numerous skin diseases ( 11 , 12 ), may occur ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Schwannomas comprise only 0.4%–1% of submucosal tumours of the GI tract 3. It has been suggested that these tumours arise from the Auerbach’s nerve plexus in the intestinal wall 4…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of primary esophageal schwannomas have been reported [3, 4]. Gastrointestinal schwannomas account for 0.4 to 1.0 % of all submucosal tumors of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%